2015
DOI: 10.1037/xlm0000063
|View full text |Cite
|
Sign up to set email alerts
|

The power of instructions: Proactive configuration of stimulus–response translation.

Abstract: Humans are characterized by an especially highly developed ability to use instructions to prepare toward upcoming events; yet, it is unclear just how powerful instructions can be. Although prior work provides evidence that instructions can be sufficiently powerful to proactively program working memory to execute stimulus-response (S-R) translations, in a reflexlike fashion (intention-based reflexivity [IBR]), the results to date have been equivocal. To overcome this shortcoming, we developed, and tested in 4 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
179
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(202 citation statements)
references
References 62 publications
22
179
1
Order By: Relevance
“…In particular, although RITL increases overall cognitive flexibility, it may also have the paradoxical side-effect of limiting flexibility in certain contexts. In particular, it has been shown that holding the intention in mind to execute a newly instructed task interferes with related (and incompatible) task performance (Meiran et al, 2015a), which we have described as an example of the classic prepared reflex effect (e.g., Hommel, 2000). We postulate that this interference – which we term the intention-based reflexivity interference effect – reveals a computational trade-off between proactive control and in-the-moment flexibility (which is aided by reactive control).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In particular, although RITL increases overall cognitive flexibility, it may also have the paradoxical side-effect of limiting flexibility in certain contexts. In particular, it has been shown that holding the intention in mind to execute a newly instructed task interferes with related (and incompatible) task performance (Meiran et al, 2015a), which we have described as an example of the classic prepared reflex effect (e.g., Hommel, 2000). We postulate that this interference – which we term the intention-based reflexivity interference effect – reveals a computational trade-off between proactive control and in-the-moment flexibility (which is aided by reactive control).…”
Section: Introductionmentioning
confidence: 82%
“…Rapid instructed task learning (RITL) is the ability to quickly perform novel instructed procedures, demonstrating successful performance even on the first trial after instruction (Cole, 2009; Cole et al, 2010a, 2013a; Liefooghe et al, 2013b; Meiran et al, 2015a). Our familiarity with this ability might make it seem mundane, yet it is remarkable from several perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…In these frameworks, abstract rules generalize prior knowledge and thus constrain the (usually) very large space of stimulus-response-outcome contingencies afforded by a novel task environment (Badre, Kayser, & D’Esposito, 2010). Such rules can both be instructed (Cohen-Kdoshay & Meiran, 2007, 2009; Cole, Bagic, Kass, & Schneider, 2010; Meiran, Pereg, Kessler, Cole, & Braver, 2015; Ruge & Wolfensteller, 2010) or transferred from prior experiences (Cole et al, 2011; Collins & Frank, 2013) to rapidly enable successful behavior in novel environments.…”
Section: Introductionmentioning
confidence: 99%
“…Within the study of human cognitive and motor control, appreciable progress has been made in describing the connection between symbolic information integration and complex action learning, opening new lines of research on how verbal instructions influence the neural and cognitive correlates of human behavior (Meiran, Liefooghe, & De Houwer, 2017;Demanet et al, 2016;Meiran, Pereg, Kessler, Cole, & Braver, 2015;Everaert, Theeuwes, Liefooghe, & De Houwer, 2014;Liefooghe, De Houwer, & Wenke, 2013;Liefooghe, Wenke, & De Houwer, 2012;Ruge & Wolfensteller, 2010). In this respect, this study aims to expand upon recent findings on the role of the lateral prefrontal cortex (LPFC) in implementing and memorizing verbal instructions at different levels of information processing and training.…”
Section: Introductionmentioning
confidence: 99%